Effects of Mixed Adding Crude Extracts of β-Glucosidases from Three Different Non-Saccharomyces Yeast Strains on the Quality of Cabernet Sauvignon Wines - Jing Liao; Shuangmei Zhang; Xiuyan Zhang (Journal of Fungi, 2022)
The aim of this study was to investigate the effects of crude extracts of β-glucosidase from Issatchenkia terricola SLY-4, Pichia kudriavzevii F2-24 and Metschnikowia pulcherrima HX-13 (termed as SLY-4E, F2-24E and HX-13E) on the flavor complexity and typicality of Cabernet Sauvignon wines. The grape must was fermented using Saccharomyces cerevisiae with single or mixed SLY-4E, F2-24E and HX-13E. The physicochemical characteristics, volatile aroma compounds, total anthocyanins and sensory attributes of the wines were determined. Adding SLY-4E, F2-24E and HX-13E in wines resulted in a decrease in the anthocyanin content, total acids and volatile acids in wines but an increase in the content of terpenes, benzene derivatives, higher alcohols and esters, which may enhance wine sensory qualities and result in loss of wine color. Different adding strategies of β-glucosidase led to a variety of effects on wine aroma. S/H/F-Ew significantly increased the content of benzene derivatives, higher alcohols and long-chain fatty acid esters, which enhanced the fruity and floral flavor of wines. F2-24E significantly increased the content of short- and medium-chain fatty acid esters, acetate esters and carbonyl compounds. The results indicated that the mixed addition of non-Saccharomyces crude extracts and co-fermentation with S. cerevisiae could further improve wine flavor quality.